Pengaruh Independensi, Profesionalisme, dan Time Budget Pressure Terhadap Kinerja Auditor dengan Skeptisme Profesional Sebagai Variabel Moderasi Pada Auditor di Kantor Akuntan Publik Kota Medan - Maura Rahma Azzahra; Yulita Triadiarti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study examines the effects of independence, professionalism, and time budget strain on auditor performance among 61 auditors in Medan City’s Public Accounting Firms (PAFs), with the moderating factor being professional skepticism. The findings, which were obtained using a quantitative survey method and SPSS analysis (multiple regression and moderated regression), demonstrate that professionalism and time budget pressure positively and significantly affect auditor performance, while independence is not significant. Professional skepticism strengthens the impact of independence on performance, negatively moderates the impact of time budget constraint on performance, and does not moderate the association between professionalism and performance, indicating the need for proportional skepticism to maintain audit quality and timeliness